(related to Lemma: Fundamental Lemma of Homogeneous Systems of Linear Equations)

Let \(\alpha_{ij}\in F\) and \(F\) be an field, and let \[\begin{array}{ccl} \alpha_{11}X_1+\ldots+\alpha_{1n}X_n&=&0\\ \alpha_{21}X_1+\ldots+\alpha_{2n}X_n&=&0\\ \vdots&\vdots&\vdots\\ \alpha_{m1}X_1+\ldots+\alpha_{mn}X_n&=&0\\ \end{array}~~~~~~~~~~~~~~~~ ( * ) \] be a homogeneous system of linear equations with \(n\) unknowns \(X_1,\ldots,X_n\) and (\(1\le m < n\)) equations. We have to show that the equation system \( ( * ) \) has a non-trivial solution.

First, we observe the following:

- It is sufficient to assume \(m=n-1\) since if we have found a non-trivial solution for this case, it is also a solution of the more general case \(m < n - 1\) (after removing some more equations from the system).
- We can assume \(\alpha_{11}\neq 0\). If in \( ( * )\) all coefficients \( \alpha_{ij} \) were zero, then any elements of the field \(F\) replacing the unknowns \(X_1,\ldots,X_n\) would be a non-trivial solution. If \(\alpha_{11}= 0\) but some other \(\alpha_{ij}\neq 0\), we can change the order of the equations by switching the \(i\)-th equation with the \(1\)-st equation and re-numbering the \(j\)-th unknown with the \(1\)-st unkonwn, so that \(\alpha_{11}\neq 0\). Note that these operations do not change the non-trivial solution, if it exists.
- We can assume that besides \(\alpha_{11}\), all other coefficients in the first column equal zero \(\alpha_{21}=\alpha_{31}=\ldots=\alpha_{m1}=0\). In order to transform the equation system into this form, we have (for \(i=2,\ldots,m\)) to multiply the first equation with \(\alpha_{i1}\) and subtract the resulting product form the \(\alpha_{11}\) multiple of the \(i\)-th equation. Note that these operations do not change the non-trivial solution, if it exists, either.

After these preparations, it is possible to prove the lemma by induction on the number of unknowns.

The equation system

\[\begin{array}{ccl} \alpha_{11}X_1+\alpha_{12}X_2&=&0\\ \end{array}\] has the solution \(X_1:=\beta_1=-\frac{\alpha_{12}}{\alpha_{11}} X_2\), \(X_2:=\beta_2\in F\).

Let the fundamental lemma be proven for \(m\ge 2\) unknowns. We have to find a non-trivial solution of the equation system \[\begin{array}{cllcl} \alpha_{11}X_1&+&\alpha_{12}X_2+\ldots+\alpha_{1n}X_n&=&0\\ 0&+&\alpha_{22}X_2+\ldots+\alpha_{2n}X_n&=&0\\ \vdots&&\vdots&\vdots&\vdots\\ 0&+&\alpha_{m2}X_2+\ldots+\alpha_{mn}X_n&=&0\\ \end{array}~~~~~~~~~~~~~~~~~~~~~(1)\] According to the base case, there exist a non-trivial solution \(b_2,\ldots,b_n\in F\) of the equation system \[\begin{array}{lcl} \alpha_{22}X_2+\ldots+\alpha_{2n}X_n&=&0\\ \vdots&\vdots&\vdots\\ \alpha_{m2}X_2+\ldots+\alpha_{mn}X_n&=&0\\ \end{array}~~~~~~~~~~~~~~~~~~~~~(2)\] Note that we have renumbered the unknowns of the smaller equation system \( (2) \) from \(X_1,\ldots,X_{n-1}\in F\) to \(X_2,\ldots,X_n\in F\) in order to better embed them into the greater equation system \( (1) \). Then the solution of the greater equation system is \(X_1:=\beta_1=-\frac{\alpha_{12}}{\alpha_{11}} X_2 -\ldots -\frac{\alpha_{1n}}{\alpha_{11}} X_n\), \(X_i:=\beta_i\in F\), \(i=2,\ldots,n\).

∎

**Koecher Max**: "Lineare Algebra und analytische Geometrie", Springer-Verlag Berlin Heidelberg New York, 1992, 3rd Volume